ANALYSIS OF THE EFFECTIVENESS OF IMPLEMENTING THE DRAWING STATE FOR THE PREPARATION OF METALWORKING BLANKS FOR MACHINES WITH CNC - ПУЗИРЬОВ, О. Л.; ГРЕЧКА, А. І. (Technologies and Engineering, 2025)
Purpose. The aim of the study is to evaluate the feasibility of using the HSLB-15 drawing line to optimize the preparation of rolled metal, ensure high accuracy of blanks, and reduce dependence on suppliers. This solution is relevant due to the need to increase production efficiency, reduce costs, and ensure the stable quality of rolled metal, which is critical for the manufacture of high-precision components widely used in mechanical engineering. Methodology. The study involved an analysis of current production processes to identify problems with the instability of rolled metal quality, which adversely affects the final products. The impact of the new technology on the economic performance of the enterprise was assessed, along with changes in raw material costs. Findings. The analysis of production processes revealed that the primary issue lies in the inconsistent quality of rolled metal provided by suppliers, which leads to increased costs and diminished accuracy of the final products. The implementation of the HSLB-15 drawing line enables the stabilization of blank quality, reduction in material waste, and optimization of production processes. The new technology significantly reduces costs associated with metal preparation, decreases reliance on external suppliers, and minimizes additional material processing operations. Economic efficiency has been confirmed: cost reductions in raw materials and improved blank quality contribute to enhancing the enterprise's competitiveness. The study demonstrated that the use of the HSLB-15 drawing line ensures high accuracy of blanks for CNC lathes, which is essential for manufacturing high-precision components. Originality. For the first time, the effectiveness of implementing the HSLB-15 drawing line for stabilizing the quality of rolled metal and optimizing the economic aspects of production processes in mechanical engineering has been demonstrated. Practical value. The introduction of this technology ensures production stability, reduces costs, improves the quality of final products, and strengthens the competitive positions of the enterprise in the market.